Maqāṣid Al-Shariah in the Contemporary Islamic Legal Discourse: Perspective of Jasser Auda - Zaprulkhan Zaprulkhan (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2018)
Nowadays, Muslims are facing various contemporary problems related to the discourse of fiqh or Islamic law. In this case, the old tradition of Islamic jurisprudence is no longer sufficient to answer those problems due to the changes in the context of space, time, culture, and contemporary sciences. Any effort to renew the aspect of methodology must be done in the field of uṣul al-fiqh not only in Islamic jurisprudence. This is the reason that methodological reconstruction is needed in order to make it is able to accommodate the various problems that are disturbing Muslims today. One of Muslim scholars who tried to reconstruct at the level of the methodology of maqāṣid al-shariah is Jasser Auda. For the purpose of reconstructing maqāṣid al-shariah fundamentally, Auda uses a philosophical approach that is multidisciplinary as well as open with various other relevant disciplines as a methodological framework for reforming the study of uṣul al-fiqh and Islamic law. Applying philosophical and historical approach this study found that Auda reconstructs maqāṣid al-shariah by offering six features: cognitive nature, wholeness, openness, interrelated hierarchy, multidimensionality, and purposefulness. Furthermore, Auda gives contribution to the development of Islamic law and human rights. This paper will explore reconstruction as well as the contribution of maqāṣid al-shariah promoted by Auda through the approach of the philosophy of the system.